Serumpun 2025: strengthening regional ties through pharmacy education and cultural exchange - Abd Wahab, Mohd Shahezwan; Ali, Aida Azlina (Faculty of Pharmacy, 2025)
From 10 to 23 July 2025, the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), welcomed delegates from Universitas Airlangga, Indonesia, for the Scholarly Engagement for Regional Understanding and Multicultural Perspectives in Pharmacy (SERUMPUN 2025) programme. This two-week mobility initiative was designed to combine combine academic excellence, practical skill development, cultural immersion, and community service, fostering a deeper understanding of pharmacy practice within the Southeast Asian context.